REDISTRIBUTION OF SNOW AND GLACIER MASS BALANCE FROM A HYDROMETEOROLOGICAL MODEL - Kuhn M. (My University, 2003)
This paper reports on the extension of a hydrometeorological model of glacierized basins to incorporate a detailed account of glacier mass balance. In this mass balance module a constant fraction of snow fall is redistributed within the basin from ice free areas to the glacier areas. In the particular basin discussed here solid precipitation on the glacier surface is increased by a factor of 2.15 over the basin mean of each 100 m altitude interval.The resulting mass balance parameters like mean annual specific balance, b(h), balance gradients, equilibrium line altitude and accumulation area ratio are within the range of records from other glaciers.The sensitivity of these quantities to meteorological input and model tuning parameters is evaluated, e.g. the sensitivity of mean specific mass balance to mean basin temperature is of the order of 800 mm/K. Emphasis is placed on the net accumulation outside the glacier areas in years with positive mass balance.
Keywords: BASIN; HYDRO-METEOROLOGICAL; HYDROLOGY